Perception of Parents and Children on Parenting in Mala, Kerala, India - Andria J. Kallarakal; Jude J. Gonsalvez (European Scientific Journal, ESJ, 2021)
Parenting styles impact the character, fate, and future of children in the family. This study on parenting styles is a reflection of the perception and views of parents and how they parent their children. The study is explorative in design. Parents are an extremely powerful force in the lives of children. The study is descriptive in nature and uses the qualitative approach. The research studies parenting styles in Mala, Kerala and more specifically the views of parents and their children on the roles of parents. The data was collected directly from the parents and their children through an interview schedule. The researchers used an interview schedule to collect information on the biopsycho-social, environmental factors that lead to the parenting styles of the subjects. The study revealed that there was a positive and significant relationship between parental permissive behaviors and their age, between parental permissive behaviors and their education, and there was a positive and significant relationship between parental permissive behaviors and their religion.